Efektivitas Teknik Relaksasi Napas dalam dan Kompres Air Hangat Menggunakan Warm Water Zak untuk Meredakan Nyeri pada Pasien Post Operasi - Rizkia Suci Pratiwi; Madyo Maryoto (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Postoperative pain is a common complaint that affects patients' comfort and quality of life, especially among the elderly who experience declining physical function. This study aims to evaluate the effectiveness of deep breathing relaxation techniques and warm compresses using a Warm Water Zag (WWZ) in alleviating postoperative pain. The research employed a descriptive case study design involving an elderly patient in Prigi Village who experienced acute pain following surgery due to a prior fall. Nursing interventions were implemented over three days, focusing on improving family health management through education and family coping support. Results indicated a significant reduction in pain after the application of deep breathing exercises and warm compress therapy. These therapies work by improving local blood circulation, relaxing muscles, and reducing physiological responses to pain through parasympathetic nervous system activation. Daily evaluations showed enhanced patient comfort and active family involvement in care. These findings suggest that a complementary combination of deep breathing relaxation and warm compresses can serve as an effective non-pharmacological intervention for postoperative pain management. Furthermore, the intervention supports increased family engagement in elderly care at home.